Effects of Isometric Handgrip Training on Resting Arterial Blood Pressure and Arterial Compliance in Medicated Hypertensive Individuals - Faulkner, Martha A. (My University, 2005)
This study examined the effects of isometric handgrip training (IHG) on resting blood pressure and resting arterial compliance in the carotid and brachial arteries of medicated hypertensive individuals. Previous studies found that isometric training reduced resting arterial blood pressure (RBP) in high-normal and medicated hypertensive individuals. Investigators have also found an improvement in central arterial compliance with aerobic training and a reduction in central arterial compliance with age, cardiovascular disease and resistance training. The effects of isometric training on arterial compliance have not been examined previously.
Ten participants participated in a one-hand IHG intervention, nine participants in a two-hand IHG intervention and 5 participants served as the non-exercising controls. Each experimental group performed four, 30% maximal voluntary IHG contractions for 2 minutes, 3 days a week, for 8 weeks. The one-hand group trained only their non-dominant hand, while the two-hand group trained both hands. Measurements of resting arterial blood pressure, and cross sectional compliance of the brachial and carotid arteries were made pre-training, after four weeks of training and after the completion of the eight-week training protocol.
There were no changes in resting arterial blood pressure after training. Mean carotid and brachial artery diameters did not change with resistance training. There were no significant changes in brachial or carotid cross sectional compliance with isometric training. In conclusion, moderated level isometric training did not elicit changes in resting arterial blood pressure and resting muscular and elastic arterial compliance in medicated hypertensive individuals compared to a non-exercising control group.
Keywords: isometric handgrip training, resting arterial pressure, arterial compliance, hypertensive